Photoneutron source based on a compact 10 MeV betatron - Chakhlov V. L. Vladimir Lukianovich; Bell Z. W.; Golovkov V. M. Vladimir Mikhailovich; Shtein M. M. Mikhail Mikhailovich (1999, 1999)
Title screen